A solution and solid state study of niobium complexes - Herbst, Leandra (University of the Free State, 2012)
This research project focused on the investigation and identification of various niobium(V) complexes containing selected O,O’-bidentate ligands that could potentially be used for the selective separation of niobium from tantalum. Emphasis was placed on acetylacetone (acacH) type of ligands due to the ease of varying their electronic and steric properties. The crystallographic characterization of three novel complexes, (acetylacetonato-κ2- O,O’)chloridotrimethoxidoniobium(V) (1), the “cage”-like structure of tetrakis- (acetylacetonato-κ2-O,O’)octakis(etoxy)tetrakis(μ2-oxo)tetraniobium(V) (2) and the two structures that were obtained from the same crystal, (1-phenyl-1,3- butanedionato-κ2-O,O’)chloridotrimethoxidoniobium(V) (3a) and (1-phenyl-1,3- butanedionato-κ2-O,O’)dichloridodimethoxidoniobium(V) (3b), is discussed and compared to literature. Complex 1 crystallized in an orthorhombic crystal system and space group Pbca, while complexes 2, 3a and 3b all crystallized in a monoclinic crystal system and a space group P21/c, for all. In general it was observed that these mono substituted β-diketonato complexes of niobium(V) crystallized in a distorted octahedral coordination polyhedron. The average O-Nb-O bite angle and Nb-O bond distance for these complexes were determined as 80.5 (1) ° and 2.108 (2) Å, respectively. A kinetic investigation was conducted to follow the formation of the (acetylacetonato- κ2-O,O’)chloridotrimethoxidoniobium(V) complex in methanol. The coordination mechanism is postulated for the two observed steps of acacH coordination, of which the initial coordination of the ligand takes place in the first step. The equilibrium constant, K1, was determined as 1975 (201) M-1 at 25.0 °C. The second, rate determining step is representative of the total reaction and includes the ring-closure of the acac ligand and yields K1 as 1403 (379) M-1. Within experimental error, this value is in good agreement with that of the first step. When comparing the rate constants, k1 and k2, it is found that the first reaction is roughly six orders of magnitude (106) faster than the slower, second reaction step. 93Nb NMR was successfully used in characterising the niobium(V) products synthesised and played an important role in the kinetic study of the project. With regards to the kinetic study; solvent coordination proceeded rapidly upon solvation of the dimeric starting material, [NbCl5]2, in methanol and the niobium(V) starting reagent was correctly determined as [NbCl2(OMe)3(MeOH)] through 93Nb NMR.

Hierdie navorsingsprojek fokus op die ondersoek en identifikasie van verskeie niobium(V)komplekse wat uitgesoekte O,O’-bidentateligande bevat wat moontlik gebruik kan word vir die selektiewe skeiding van niobium en tantalum. Klem is gelê op asetielasetoon (acacH) tipe ligande as gevolg van die maklike manier waarop hulle elektroniese en steriese eienskappe verander kan word. Die kristallografiese karakterisering van drie nuwe komplekse, (asetielasetonato-κ2- O,O’)chloridotrimetoksidoniobium(V) (1), die “hok”-agtige struktuur tetrakis- (asetielasetonato-κ2-O,O’)oktakis(etoksi)tetrakis(μ2-okso)tetraniobium(V) (2) en die twee strukture wat verkry is vanuit dieselfde kristal, (1-feniel-1,3-butaandionato-κ2- O,O’)chloridotrimetoksidoniobium(V) (3a) en (1-feniel-1,3-butaandionato-κ2-O,O’)dichloridodimetoksidoniobium( V) (3b), word bespreek en vergelyk met literatuur. Kompleks 1 kristalliseer in `n ortorombiese kristalstelsel en ruimtegroep Pbca, terwyl komplekse 2, 3a en 3b almal in `n monokliniese kristalstelsel en ruimtegroep P21/c, kristalliseer. Oor die algemeen is dit waargeneem dat hierdie mono-gesubstitueerde β-diketonato komplekse van niobium(V) in `n verwronge oktahedriese koördinasie polyheder kristalliseer. Die gemiddelde O-Nb-O bythoek en Nb-O bindingsafstand vir hierdie komplekse is onderskeidelik as 80.5 (1) °en 2.108 (2) Å bepaal. `n Kinetiese ondersoek is uitgevoer om die vorming van die (asetielasetonato-κ2- O,O’)chloridotrimetoksidoniobium(V)kompleks in methanol te volg. Die koördinasiemeganisme is gepostuleer vir die twee waargenome stappe van acacH koördinasie, waarvan die aanvanklike koördinasie van die ligand in die eerste stap plaasvind. Die ewewigskonstante, K1, is as 1975 (201) M-1 teen 25.0 °C bepaal. Die tweede, tempobepalende stap is verteenwoordigend van die totale reaksie en sluit die ring-sluiting van die acac ligand in, en lewer K1 as 1403 (379) M-1 op. Binne eksperimentele fout stem hierdie waarde goed ooreen met die waarde van die eerste stap. Wanneer die tempokonstantes, k1 en k2, vergelyk word is, gevind dat die eerste reaksie ongeveer ses ordegroottes (106) vinniger as die stadiger, tweede reaksie stap is. 93Nb KMR is met sukses gebruik in die karakterisering van die bereide niobium(V) produkte en speel `n belangrike rol in die kinetiese studie van die projek. Met betrekking tot die kinetiese studie vind oplosmiddel-koördinasie vinnig plaas met oplossing van die dimeriese reagens, [NbCl5]2, in methanol en die niobium(V) reagens is korrek vasgestel as [NbCl2(OMe)3(MeOH)] deur middel van 93Nb KMR.
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2012
Keywords: X-ray crystallography; Infrared spectroscopy; Nuclear magnetic resonance spectroscopy; Niobium compounds -- Synthesis; Niobium compounds -- Analysis